The effect of project governance and sustainability on project success of the public sector organizations in Pakistan - Irfan, Muhammad; Hassan, Mazlan (Universiti Putra Malaysia Press, 2019)
The purpose of this paper is to investigate the effect of project governance and sustainability on project success of the public sector organizations in Pakistan. Across Pakistan, 425 valid responses were collected using a cross-sectional survey. The sample was restricted to firms registered with Pakistan Engineering Council. PLS-SEM was used to assess the proposed reflective-formative model through path modeling and bootstrapping technique. The results indicate that project governance and sustainability are positively associated with project success. This paper provides empirical evidence about the substantial positive effect of project governance and sustainability on project success, in the context of public sector organizations in Pakistan.